Eating behaviors moderate the associations between risk factors in the first 1000 days and adiposity outcomes at 6 years of age. Issue 5 (27th March 2020) - Fogel, Anna; McCrickerd, Keri; Aris, Izzuddin M; Goh, Ai Ting; Chong, Yap-Seng; Tan, Kok Hian; Yap, Fabian; Shek, Lynette P; Meaney, Michael J; Broekman, Birit F P; Godfrey, Keith M; Chong, Mary F F; et al.
ABSTRACT: Background: Several risk factors in the first 1000 d are linked with increased obesity risk in later childhood. The role of potentially modifiable eating behaviors in this association is unclear. Objectives: This study examined whether the association between cumulated risk factors in the first 1000 d and adiposity at 6 y is moderated by eating behaviors. Methods: Participants were 302 children from the GUSTO (Growing Up in Singapore Towards healthy Outcomes) cohort. Risk factors included maternal prepregnancy and paternal overweight, excessive gestational weight gain, raised fasting plasma glucose during pregnancy, short breastfeeding duration, and early introduction of solid foods. Composite risk scores reflecting the prevalence and the importance of the risk factors present were computed. Adiposity outcomes were child BMI and sum of skinfolds (SSF), and candidate eating behavior moderators were portion size, eating rate, and energy intake during lunch and in an eating in the absence of hunger task. Results: Higher composite risk score predicted higher BMI z scores (B = 0.08; 95% CI: 0.04, 0.13) and larger SSF (0.70 mm; 0.23, 1.18 mm), and was associated with larger self-served food portions (5.03 kcal; 0.47, 9.60 kcal), faster eating rates (0.40 g/min; 0.21, 0.59 g/min), and larger lunch intakes (7.05 kcal; 3.37, 10.74 kcal). Importantly, the association between composite risk score and adiposity was moderated by eating behaviors. The composite risk score was unrelated to SSF in children who selected smaller food portions, ate slower, and consumed less energy, but was positively associated with SSF among children who selected larger food portions, ate faster, and consumed more energy (eating behavior × risk score interactions: P  < 0.05). Conclusions: The association between risk factors in the first 1000 d and adiposity at 6 y varies by eating behaviors, highlighting modifiable behavioral targets for interventions. This trial was registered at clinicaltrials.gov as NCT01174875.